Efektifitas Ekstrak Daun dan Getah Tanaman Jarak Cina (Jatropha Multifida L) Sebagai Antibakteri terhadap Pertumbuhan Bakteri Staphylococcus Aureus Secara In Vitro - Anggita, Dwi; Yusriani, Yusriani; Abdi, Dian Amelia; Desiani, Vivin (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
Jatropha multifida L. contains alkaloids, tannins, flavonoids, saponins and phenolic acids that differ from each part of the plant and the content of these substances is what makes L. multifida Jatropha has a function as an antibacterial so that the leaf extract and the gap of chinese distance ( Jatropha multifida L.) allegedly capable of inhibiting the growth of Staphylococcus aureus bacteria. The aim of this research was to know the effectivity of leaf extract and gum of Jatropha multifida L. to the growth of Staphylococcus aureus bacteria in vitro.Penelitian used true experimental post test design. Using disc diffusion method with concentration 25; 50; 75; and 100% v / v leaf and gum china distance. Positive control was used Clindamycin 5Î¼g drip antibiotic paper disc. The data were analyzed descriptively. The result of the research showed the difference of different inhibition zone between treatments. In chinese leaf extracts showed different mean diameters, at concentrations of 25%, 50%, 75% with inhibit zone formed respectively 0 mm, 9.32 mm, and 17.48 mm and the highest inhibition zone at concentration of 100% with an average diameter of 22.24 mm. In the gap of chinese distance showed a different mean diameter, at concentrations of 25%, 50%, 75% with the inhibit zone formed respectively 16.08 mm, 18.15 mm, and 18.63 mm and the highest inhibition zone at a concentration of 100% with an average diameter of 21.91 mm. Clindamycin positive controls show an average inhibit zone of 23.31 mm. It was concluded that there was an effect of leaf extract and resin of chinese distance plant (Jatropha multifida L.) on growth of Staphylococcus aureus bacteria, and the best concentration was 100% concentration and almost closer to the inhibitory zone of Clindamycin antibiotics as positive control.